KONTRIBUSI PT. NEWMONT NUSA TENGGARA (PT. NNT) TERHADAP PENINGKATAN PENDIDIKAN DI DAERAH LINGKAR TAMBANG - Wiwien Kurniawati (Universitas Pendidikan Mandalika, 2016)
This study aimed to determine the extend to which the commitment and contribution of PT. NNT to education circumference area of the mine. The reason of PT. NNT has a CSR program which is based on four pillars, namely in the fields of education, health, economic and environmental.This research is qualitative with descriptive type of research that is supported by quantitative data. The subject of this research is the progrmes CSR of PT. Newmont Nusa Tenggara. Methods of data collection is done by observation, interviews, documentation, and questionnaires. And validity of a survey conducted by the triangulation approach of data source triangulation and triangulation methods. This study uses a model of interactive analysis techniques. Contains a component process analysis data reduction, data presentation, and drawing conclusions. The results showed as follows. (1) PT. NNT has a strong commitment to education. (2) PT. NNT to implementation the programes of CSR to education such as physical and non-physical. (3) the contribution of PT. NNT tophysical is efective and the contribution non-physical is low.